Democracy without Citizens : Media and the Decay of American Politics. - Entman, Robert M. (Oxford University Press, 1989)
In this book, Professor Entman offers a penetrating critique of American journalism and the political process. He identifies what he considers the key dilemma facing today's reporters and editors: the catch-22 that prevents the news media from offering in-depth quality journalism, which would create a sophisticated citizenry, because it does not already have a sophisticated audience. He continues on to examine the effects and offer possible solutions to this dilemma. In the course of his analysis, Entman sheds considerable light on such issues as the sources and bias of the news, the relations.